2022
DOI: 10.1021/acs.analchem.2c03577
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Channel Fluorescent Probe for the Detection of Peroxynitrite and Glutathione in Mitochondria: Accurate Discrimination of Inflammatory and Progressing Tumor Cells

Abstract: Distinguishing between normal, inflammatory, and progressing tumor cells plays a vital role in early diagnoses and clinical studies. The simultaneous quantification of multiple biomarkers in cells can reveal cellular heterogeneity, which contributes to the discrimination of different types of cells. Herein, a dual-channel fluorescent probe has been developed for monitoring peroxynitrite (ONOO–) and glutathione (GSH) to accurately discriminate normal cells, inflammatory cells, and progressing cancer cells. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…One typical targeting ligand is triphenylphosphonium (TPP). Utilizing it as the mitochondria targeting group, Zhang et al reported a dual-channel fluorescent probe 30 ( NTG ) for simultaneous detection of GSH and ONOO - in mitochondria [ 75 ]. Probe 30 could respond to GSH and ONOO - in two channels; an enhanced fluorescence was recorded in the red channel (670 nm) in the presence of GSH, while another increased emission was found in the green channel (530 nm) in the simultaneous presence of GSH and ONOO − , whereas ONOO − could afford only weak fluorescence in the green channel ( Figure 8 A,B).…”
Section: Design Strategies For Specific Fluorescent Probes For Intrac...mentioning
confidence: 99%
“…One typical targeting ligand is triphenylphosphonium (TPP). Utilizing it as the mitochondria targeting group, Zhang et al reported a dual-channel fluorescent probe 30 ( NTG ) for simultaneous detection of GSH and ONOO - in mitochondria [ 75 ]. Probe 30 could respond to GSH and ONOO - in two channels; an enhanced fluorescence was recorded in the red channel (670 nm) in the presence of GSH, while another increased emission was found in the green channel (530 nm) in the simultaneous presence of GSH and ONOO − , whereas ONOO − could afford only weak fluorescence in the green channel ( Figure 8 A,B).…”
Section: Design Strategies For Specific Fluorescent Probes For Intrac...mentioning
confidence: 99%
“…14,15 However, they are usually focused on the detection of the sum of biological thiols, and show poor discrimination ability for GSH from the other two, due to the relatively high content, homogeneity in structure and reactivity of GSH, Cys, and Hcy. 16,17 Even though several works about selective detection of GSH have been reported, they still face the limitations of the utilization of toxic organic substances and heavy metal ions, low stability, and complicated molecular design and synthesis of the fluorescent probes. 9,16 Thus, it is still an urgent and challenging task to develop effective strategies for designing fluorescence assays for GSH with high sensitivity and discrimination ability to other biological thiols.…”
mentioning
confidence: 99%
“…16,17 Even though several works about selective detection of GSH have been reported, they still face the limitations of the utilization of toxic organic substances and heavy metal ions, low stability, and complicated molecular design and synthesis of the fluorescent probes. 9,16 Thus, it is still an urgent and challenging task to develop effective strategies for designing fluorescence assays for GSH with high sensitivity and discrimination ability to other biological thiols.…”
mentioning
confidence: 99%
“…The traditional method for intracellular GSH measurement is the enzymatic recycling assay. Glutathione reductase (GR) and NADPH are required during the operation, so this method is costly with tedious and time-consuming sample pretreatment. , Although LC-MS is also widely used for the detection of thiols, cost-effective and portable measurement is not allowed. , Fluorescent probes have recently emerged as indispensable and ideal tools to monitor molecular events for real-time monitoring in multiple research fields due to their simple operation, high selectivity, and good biocompatibility. To date, plenty of fluorescent probes for detecting GSH have been reported based on different mechanisms, e.g., cleavage of sulfonamides/sulfonate esters/Se–N bond, disulfide bond exchange, aryl substitution reactions, Michael addition followed by cyclization, and metal ion replacement followed by coordination. In addition, several probes for the real-time quantification of GSH have been developed. The fly in the ointment is that thiol-containing proteins are ubiquitous in cells (up to 70% of the total cellular thiols), the interference of which is not considered by most GSH probes in cell imaging. In addition, there are relatively few studies using probes to quantify the total GSH (tGSH), GSH, and GSSG in cells and tissues.…”
mentioning
confidence: 99%
“…15,16 Fluorescent probes have recently emerged as indispensable and ideal tools to monitor molecular events for real-time monitoring in multiple research fields due to their simple operation, high selectivity, and good biocompatibility. 17−21 To date, plenty of fluorescent probes for detecting GSH have been reported based on different mechanisms, e.g., cleavage of sulfonamides 22 /sulfonate esters 23 /Se−N bond, 24 disulfide bond exchange, 25 aryl substitution reactions, 26 Michael addition followed by cyclization, 27 replacement followed by coordination. 28−30 In addition, several probes for the real-time quantification of GSH have been developed.…”
mentioning
confidence: 99%